Answer:
4x + 1
Step-by-step explanation:
note that (f + g)(x) = f(x) + g(x) , thus
f(x) + g(x)
= x + 3x + 1 ← collect like terms
= 4x + 1
Answer:
D) x = 4, y = -2, z = 3
Step-by-step explanation:
x = 3z − 5
2x + 2z = y + 16
2(3z - 5) + 2z = y + 16
6z - 10 + 2z = y + 16
8z = y + 26 ---> (A)
7x − 5z = 3y + 19
7(3z - 5) - 5z = 3y + 19
21z - 35 - 5z = 3y + 19
16z = 3y + 54 ---> (B)
8z = y + 26
16z = 3y + 54
2(y + 26) = 3y + 54
2y + 52 = 3y + 54
y = -2
8z = -2 + 26
8z = 24
z = 3
x = 3(3) - 5
x = 4
Hey there!
Let's write an equation given this information. We will use x to represent the number.
2(x-7)=5
Now, we use the distributive property to remove the parentheses.
2x-14=5
Now, we add 14 to both sides.
2x=19
We divide both sides by 2.
x=9.5
Therefore, our number is 9.5
I hope this helps!
Answer:
7/5 y --> y+ 2/5y
0.68y --> y - 0.32y
3/5y --> y - 2/5y
1.32y --> y+ 0.32y
Step-by-step explanation:
Pretend there is a 1 in front of each y that doesn't have a number (coefficient) in front of it. 1 = 5/5, and then just solve for the fraction expressions.
Answer:
24
Step-by-step explanation:
3 x 1/72 = 1 mile
72/3 = 24
The car will use 1 gallon of gas per 24 miles